1997
DOI: 10.1021/ja9616950
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin Mixed-Valence π-Cation Radicals:  Solution Stability and Properties

Abstract: Solution equilibria and optical spectra of several metallooctaethylporphyrin π-cation radicals have been examined in methylene chloride solution. The several π-cation radical species, [M(OEP•)]Y (M = Cu, Ni, Zn, Pd, or VO; Y = ClO4 - or SbCl6 -), are found to dimerize to form [M(OEP•)]2 2+. These dimeric species are characterized by the appearance of a new, strongly concentration-dependent near-infrared absorption band. This band is found in the region of 900−960 nm for all compounds except for the vanadyl com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 69 publications
7
37
0
Order By: Relevance
“…Similar phenomena were reported for the radical derivatives of some other metalloporphyrins (29,31). Subsequent crystallization studies demonstrated that the cation porphyrin radicals formed tight dimeric complexes in a face-to-face manner with an interplanar separation distance smaller than 3.5 Å (35).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Similar phenomena were reported for the radical derivatives of some other metalloporphyrins (29,31). Subsequent crystallization studies demonstrated that the cation porphyrin radicals formed tight dimeric complexes in a face-to-face manner with an interplanar separation distance smaller than 3.5 Å (35).…”
Section: Resultssupporting
confidence: 58%
“…4B) (4,(28)(29)(30)(31)(32)(33). We term the former case with an odd number of spin/charge as type I CR and the latter case with an even number as type II CR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These designations would indicate that the two Π systems ( i,e ., the hemes) share two holes. In contrast, the Compound II-like state would be considered a type I CR, (Π) 2 +• complex where the Π systems have a single hole distributed over both sites [37]. …”
Section: Discussionmentioning
confidence: 99%
“…[9] Thus, much attention has been focused on the electronic interactions between two or more porphyrins in the oxidized state from the point of view of bio-inspired chemistry [6,[10][11][12][13][14][15] in addition to supramolecular chemistry in the design of highly organized assemblies that consist of porphyrin p systems.…”
Section: Introductionmentioning
confidence: 99%